Investigating the dimensions of students’ interaction in listening online learning environment amidst Covid-19 pandemic - Arum Nisma Wulanjani; Candradewi Wahyu Anggraeni; Sukma Shinta Yunianti (Universitas Pendidikan Indonesia, 2022)
The existence of the COVID-19 pandemic forces the Indonesian government to carry on online learning at all education levels, to keep the teaching and learning going on. For students, this ongoing online learning has brought about various impacts on their online learning success. One important factor determining online learning success is students’ interaction. Thus, paying more attention to whether an online learning environment has promoted the students’ interaction is crucial to creating successful online learning. This study aimed to investigate the dimensions of students’ interaction in the online listening learning environment. Moreover, this study also tried to explore how students perceived the interaction in the online listening learning environment. There were 78 students majoring in English Education as participants in this study. A convergent mixed-method was applied in this study, in which the results of the quantitative and qualitative data analysis were brought together. A modified questionnaire of OLLES (Online Learning Environment Survey) and a close-ended interview were carried out to gather the data. The results showed that the dimensions of interaction in the online listening learning environment had a statistically significant high rating. The interaction between the lecturer and the students placed the highest among all of the dimensions. Overall, all the dimensions of interaction in online listening learning were highly perceived by the students. The implications suggested that providing well-designed authentic materials, collaborative activities, and asynchronous models were needed to support the students’ online learning performance.